MASS MEDIA COMMUNICATION IN RELATION TO SLOVAK FOOTBALL FROM THE PROSPECTIVE OF DIFFERENT SOCIAL GROUPS (Fiep Bulletin - online, 2011)
Media are participating on a creation of a public opinion on different issues or matters in general and sport, in this case football, doesn't represent any exception. Mass media are more than prepared for any positive change within the Slovak football, which would bring brighter future for everyone involved in it. At the moment media's opinion on different aspects of Slovak football, such as infrastructure, sports quality of performances, fair play or fair competition, is rather negative, but definitely most of the time realistic, because when the things are not working as they are supposed to, there are not many possibilities to present it in a positive view. Truly, but also little bit more positively are the media presenting the football from the prospective of the Slovak national team, especially due to its actually impressive results over the period of last few seasons.It is necessary not to increase only professionalism and popularity of football in Slovakia, but first of all find its respected place and status within the society. More trust and better image would also lead to a better presentation of the football by the media.